Standard-setters Versus Big4 Opinion, Concerning IASB Revision Project of the Conceptual Framework for Financial Reporting. The Case of Presentation and Disclosures Chapter - Burca, Valentin; Mateș, Dorel; Pușcaș, Adriana (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
On the last decades the accounting system haven‘t been able to follow the dynamics of the economic systems generated by the globalization process. In order to reduce the lag between the demand of financial information and the offer of financial information, IASB has started numerous initiatives aiming the increase on the quality of the financial information. Among the current list of current IASB major projects there is also the project of revising the actual conceptual framework for financial reporting. This study is designed to give some directions that will be considered on the exposure draft of this project, analyzing the comment letters submitted by the members of ASAF and the Big4 as well. The study reveals the increasing importance the preparers and users give to the disclosures included on the notes to the primary financial statements. Moreover, on this study we emphasize several challenges that IASB has to face on issuing the exposure draft for this important project. Some of the main challenges refer to the narrow scope of the financial statements, the criteria used on classification, aggregation and offsetting, or the use of the materiality concept.